Use of cerium oxide nanoparticles: a good candidate to improve skin tissue engineering. (26th March 2019) - Pesaraklou, Atefeh; Mahdavi-Shahri, Nasser; Hassanzadeh, Halimeh; Ghasemi, Masoud; Kazemi, Mahboubeh; Mousavi, Nasser Sanjar; Matin, Maryam M
Abstract: Today advancements in nanotechnology have made extensive progress in tissue engineering. Application of cerium oxide nanoparticles (CeO2 ) has improved regenerative medicine due to their antioxidant properties. In this study, nanoparticles were used to increase the efficacy of skin substitutes. Human skin samples were decellularized using four methods and studied via histological stainings and DNA content analyses. Then CeO2 dispersing and its stability were investigated. The prepared acellular dermal matrices (ADMs) were immersed in CeO2 suspension and their effects were evaluated on growth of cultured human adipose derived-mesenchymal stem cells (hAd-MSCs) using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay and histological methods. Moreover, their antioxidant properties were assessed based on DPPH degradation. Changes in the collagen contents of the scaffolds containing cells and CeO2 were also determined by electron microscopy and their tensile strength was compared to ADM. Our results indicated that use of trypsin/NaOH protocol resulted in most efficient cell removal while maintaining extracellular matrix (ECM) architecture. Among different dispersal methods, the approach using Dulbecco's modified Eagle's medium (DMEM), wetting with fetal bovine serum (FBS) and ultrasonic bath resulted in the best stability. Furthermore, it was shown that CeO2 not only had no toxicity on the cells, but also increased the growth and survival of hAd-MSCs by about 27%, improved free radical scavenging, as well as the amount of collagen and tensile strength of the scaffolds containing nanoparticles compared to the ADM. It can be concluded that the combination of ADM/CeO2 /hAd-MSCs could be a step forward in skin tissue engineering.